Pertumbuhan Dan Produksi Dua Varietas Kedelai Pada Cekaman Kekeringan - Josua Simanjuntak; Chairani Hanum; Diana Sofia Hanafiah (Universitas Sumatera Utara, 2015)
These research conducted in North Sumatera university agricultural faculty in January to April 2014, using factorial randomized block design with two factors. The first factor is the soybean variety (Anjasmoro and Wilis) and the second factor is treatment drought stress (optimum field capacity, and drought stress treatment beginning flowering plant for 14 days).The results of these research showed that drough stress decrease growth and production parameter were leaf area (25,40%), root volume (44,87%), shoot dry weight (38,01%), and dry weight of 100 seeds (23,32%).Keywords :growth, Anjasmoro, Wilis, drought stress.